2021
DOI: 10.1177/23821205211006392
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Medical Student Mental Health during COVID-19: Strategies Implemented for an Accelerated Curriculum Medical Campus

Abstract: Medical student education has not been immune to life altering changes of the global Coronavirus disease 2019 (COVID-19) pandemic. Pre-pandemic anxiety and mental health concerns were already a significant problem in the world of medical student education. Educators are reformulating strategies to address the increased demand for mental health services and wellness during COVID-19. Adaptations include increased and varied internal and student focused communication, as well as new support structures built aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…[37][38][39][40] Institutions have recognised the impact of the ongoing public health crisis, initiating meaningful actions such as regular staff check-ins, virtual social events or communiques promoting well-being and sharing mental health resources. 21,22,41,42 The community is also having new conversations about burnout and even finding new terms to describe how we are feeling, like languishing. 43 However, it remains to be seen whether the medical education community will-or will feel permitted to-carry forward the increased flexibility and autonomy the COVID-19 pandemic provided for some.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37][38][39][40] Institutions have recognised the impact of the ongoing public health crisis, initiating meaningful actions such as regular staff check-ins, virtual social events or communiques promoting well-being and sharing mental health resources. 21,22,41,42 The community is also having new conversations about burnout and even finding new terms to describe how we are feeling, like languishing. 43 However, it remains to be seen whether the medical education community will-or will feel permitted to-carry forward the increased flexibility and autonomy the COVID-19 pandemic provided for some.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the start of the pandemic, conversations about wellness and burnout seem to have gained a new sense of urgency—and perhaps even legitimacy 37–40 . Institutions have recognised the impact of the ongoing public health crisis, initiating meaningful actions such as regular staff check‐ins, virtual social events or communiques promoting well‐being and sharing mental health resources 21,22,41,42 . The community is also having new conversations about burnout and even finding new terms to describe how we are feeling, like languishing 43…”
Section: Discussionmentioning
confidence: 99%
“…We are currently living through an interval of unexpected vulnerability in our learning environments. Even prior to the COVID‐19 syndemic, mental health was a significant concern in health professions education, particularly among learners and educators from historically excluded groups (Chandratre, 2020; Chandratre et al, 2021; Schindler et al, 2021; Sharma & Bhaskar, 2020). We know that frontline medical professionals are at risk of psychological distress (Galbraith et al, 2021), but the plights of health professions learners and educators during COVID‐19 has drawn more limited attention (Li et al, 2021; Molodynski et al, 2021; Schwenk et al, 2010; Sotto‐Santiago, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Despite being in the business of training healthcare professionals, we are not considered part of the healthcare workforce. It has been suggested that health professions environments are especially vulnerable during the syndemic (Chandratre, 2020; Chandratre et al, 2021; Melnyk et al, 2021; Schindler et al, 2021), which may have an impact on the future of health care. Learners and educators thus require tailored support, distinct from the general population or medical professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Amidst this upheaval, medical students have been subject to vast amounts of disruption such as the cancellation of clinical placements and severe restrictions on the patients they are allowed to interact with. It is known that medical students already suffer from greater levels of mental health disorders, stress, and burnout compared to the general public, and this has only been heightened by the uncertainty of the COVID-19 pandemic [5,6].…”
Section: Discussionmentioning
confidence: 99%